Pd-Catalyzed Asymmetric Allylic Substitution Cascade via Desymmetrization for the Construction of Chiral Polyheterocycles - Kou, Xuezhen; Xu, Yongjin; Dong, Siqi; Liu, Hui; Liu, Delong; Zhang, Wanbin (Pharmaceutical Fronts, 2024)
Chiral polyheterocycles represent an important class of compounds because of their prevalence in bioactive natural products and chiral drugs. Pd-catalyzed allylic substitution is a powerful synthetic tool for forming C–C and C–X bonds (X = N, O, S, etc.). Naturally, asymmetric cascade reactions that utilize allylic substitution are undoubtedly efficient pathways to construct heterocycles. In this article, we reviewed the Pd-catalyzed asymmetric allylic substitution cascade via the desymmetrization of meso-diol diesters of cycloolefins, for the construction of chiral polyheterocycles and their derivatives.
Keywords: Pd-catalyst; asymmetric cascade allylic substitution; desymmetrization; chiral polyheterocycles; synthesis